Protected Areas and Endemic Freshwater Fishes of the Cape Fold Ecoregion: Missing the Boat for Fish Conservation? - Jordaan, Martine S.; Chakona, Albert; van der Colff, Dewidine (Frontiers in Environmental Science, 2020)
Freshwater systems and their associated biodiversity are among the most threatened ecosystems globally. The Cape Fold Ecoregion (CFE), located within the Western and Eastern Cape Provinces of South Africa, is home to the highest percentage of threatened freshwater fish in the country. The main threats to native fish in this region are predation and competition from invasive alien fishes and habitat degradation. The region has an extensive protected area (PA) network that protects a wide array of ecosystems, but limited information exists on the role of PAs in conserving freshwater fishes in the region. This study evaluated the value of PAs for protection of freshwater fishes in the Western Cape Province by setting species conservation targets and then intersecting species distribution data using protected area polygons. Conservation targets were set following the minimum viable population required for long-term persistence, a minimum of 10 subpopulations. This, along with other factors such as population viability and PA effectiveness was used to determine whether a species was effectively protected by the current PA network. Species were classified into one of four categories; 1) well protected, 2) moderately protected, 3) poorly protected and 4) not protected. Our results indicate that the majority of native fish species are inadequately protected within the current PA network in the province, mainly a result of the linear nature of riverine ecosystems that increases its sensitivity to threats outside of the PA. The implications of the results for protected area expansion and management for improved conservation of native fish are discussed.